2021
DOI: 10.1007/s40266-021-00877-z
|View full text |Cite
|
Sign up to set email alerts
|

Current Insights into Treating Vertigo in Older Adults

Abstract: The number of older people has been increasing over recent decades in Western populations. Dizziness, imbalance, and vertigo constitute some of the most common complaints in older patients, and risk of falling is the most frequent and worrying consequence. It has been reported that 15-20% of the adult population experiences these debilitating symptoms. Among the diseases that may be associated with vertigo, the three classes of otological, central, and functional (psychological) dizziness may be distinguished.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 119 publications
1
30
1
4
Order By: Relevance
“…It is reported that ET and CGRP function together for the regulation of blood flow and maintaining vascular function (Parlapiano et al, 1999). Studies have found that cervical vertigo development is closely associated with the imbalance in the production of ET-1 and CGRP and these two factors serve as important pathogenetic factors for the disorder (Casani et al, 2021;Wang et al, 2007). It has been found that regulation of ET-1 and CGPR levels in plasma dilates blood vessels of the brain as well as the inner ear thereby exhibiting a therapeutic effect on vertigo (Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that ET and CGRP function together for the regulation of blood flow and maintaining vascular function (Parlapiano et al, 1999). Studies have found that cervical vertigo development is closely associated with the imbalance in the production of ET-1 and CGRP and these two factors serve as important pathogenetic factors for the disorder (Casani et al, 2021;Wang et al, 2007). It has been found that regulation of ET-1 and CGPR levels in plasma dilates blood vessels of the brain as well as the inner ear thereby exhibiting a therapeutic effect on vertigo (Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 30% of individuals over the age of 60 and nearly 50% of individuals over the age of 85 suffer from vertigo (2). Vertigo is a significant risk factor for falls in older adults and a remarkable cause of disability in those over 65 (3,4).…”
Section: Epidemiologymentioning
confidence: 99%
“…Its key characteristics are the presence of rapidly-discharging EEG activity and a favorable response to antiepileptic therapy ( Hewett and Bartolomei, 2013 ). On the other hand, several anticonvulsants including diazepam, gabapentin and carbamazepine are used to treat several vestibular disorder subtypes, even those unrelated to seizures ( Casani et al, 2021 ). CBD is a proposed drug indicated for treating epilepsy.…”
Section: The Cannabinoid System and The Vestibular Pathwaymentioning
confidence: 99%